The benefit of a geriatric nurse practitioner in a multidisciplinary diagnostic service for people with cognitive disorders - Ament, Bart H L (BMC Res Notes, 2015)
BACKGROUND: The aim of the study was to evaluate whether adding a geriatric nurse practitioner (GNP) to an outpatient diagnostic multidisciplinary facility for patients with cognitive disorders (Diagnostic Observation Center for PsychoGeriatry, DOC-PG) could improve quality of care. DOC-PG combines hospital diagnostics and care assessment from a community mental health team and provides the general practitioner (GP) with advice for treatment and management. In a previous study, we found that 28.7% of the advice made by this service was not followed up on by the GP. METHODS: Two cohorts were studied: a group of patients with added GNP (n = 114) and a historical reference sample (n = 137). Both groups followed the same diagnostic protocol and care approach, but, in the GNP group, a care coordinator was added in order to communicate the advice from the DOC-PG to the GP. The primary outcome was the concordance rate of GPs regarding the advice. At the patient level, health-related quality of life (HRQoL) was assessed. Self-Rated Burden and care-related quality of life were measured at the informal caregiver level. Measures were conducted immediately after DOC-PG diagnosis and after 6 and 12 months. Univariate analyses, logistic regression analyses, and mixed model multilevel analyses were used to test differences between both groups. RESULTS: Total concordance rates were significantly higher in the GNP group compared to the reference sample (82.1 and 71.3%, respectively; p < 0.001). No improvement in patient HRQoL was identified. Among the informal caregivers, a significant reduction of Self-Rated Burden was found in the GNP group at 12 months (adjusted mean difference −1.724, 95% CI −2.582 to −0.866; p < 0.001). CONCLUSIONS: Adding a GNP to an outpatient diagnostic multidisciplinary facility for patients with cognitive disorders may improve the GP concordance rate of the advice from the DOC-PG and reduce subjective burden of the informal caregiver.